HyperCKemia associated with acupuncture: a case report and review of the literature - Xiaochan Tan; Wei Liu; Yuzheng Du; Xianggang Meng; Xuemin Shi (BMC, 2022)
Abstract Background Acupuncture therapy has been widely used as an alternative therapy to treat multiple diseases, such as sequelae of stroke, pain, facial paralysis and so on. In recent years, few adverse events related to acupuncture treatment have been reported, among which hematoma, bleeding and dizziness are the main manifestations. However, to date, there have been no existing cases reported the association between acupuncture therapy and asymptomatic/pauci-symptomatic hyperCKemia. Case presentation We report a patient who developed hyperCKemia during 5 sessions of acupuncture at different frequencies. After stopping acupuncture treatment for 1 month, follow-up showed a significant downward trend in serum creatine kinase (sCK). However, after that this patient started to get acupuncture treatment again in order to improve the sequelae of stroke. Meantime, the sCK rose again. Conclusion HyperCKemia may associated with acupuncture therapy. All kinds of adverse events of acupuncture should be recorded comprehensively and objectively so as to improve the safety standard system of acupuncture therapy.